Analysis of Development Inequality and Leading Sectors in North Kalimantan - Banurea, Nike Hernawati; Benardin (Formosa Journal of Multidisciplinary Research, 2024)
The purpose of this study was to determine inequality and leading economic sectors in North Kalimantan with a period of 6 years from 2018 to 2023. The research method used is to use Williamson index calculation and analyze the leading sectors through the calculation of Location Quotient, Shift Share and Klassen typology. By taking secondary data obtained from the source of the Central Bureau of Statistics of North Kalimantan. The results showed that inequality in North Kalimantan from 2018 to 2023 from Williamson's index calculation was relatively high . While the calculation of the leading sector in North Kalimantan is the forestry sector, agriculture, warehousing, mining, transportation, construction and fisheries which is the biggest competitiveness is excavation and mining. The implication of these results is the need for more inclusive policies to reduce development inequality and increase the contribution of leading sectors in the economic growth of the region.